IDENTIFIKASI DAERAH PROSPEK PANAS BUMI BERDASARKAN SEBARAN TEMPERATUR DAN STRESS VEGETASI MENGGUNAKAN CITRA LANDSAT 8 DI DAERAH GUNUNG TAMPUSU - Ginevra Dagna Clarissa; Cyrke A. N. Bujung; Patricia M. Silangen (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2020)
Mount Tampusu is a mountain located in North Sulawesi Province, Indonesia. Mount Tampusu is a mountain flanked by two lakes resulting from volcanic activity, namely Lake Linow and Lake Tondano, also around Mount Tampusu, there are geothermal manifestations such as hot water pools and steamy soils. The surface temperature around Mount Tampusu has changed from year to year. Whether the changes occur significantly or only slightly, surely it affects the vegetation around the mountain. The purpose of this study was to determine the surface temperature and vegetation stress in the area of ​​geothermal manifestation around Mount Tampusu based on the Remote Sensing Method. In this study, the analysis uses Landsat 8 satellite imagery in 2020. The value of surface temperature is obtained from the thermal band processing of Landsat 8 satellite imagery which is then correlated with the vegetation index value obtained from NIR and Red band processing using the correlation method. The results showed that the high vegetation index was in the manifestation area with a value of 0.58. The value of the influence of surface temperature on vegetation -0.70596. A negative value (-) means that the vegetation and surface temperature are inversely correlated. The higher the vegetation, the lower the surface temperature value and vice versa, the higher the surface temperature, the lower the vegetation index.